Effect of galvanic vestibular stimulation applied at the onset of stance on muscular activity and gait cycle duration in healthy individuals - Abbariki, Faezeh; Mikhail, Youstina; Hamadjida, Adjia; Charron, Jonathan; Mac-Thiong, Jean-Marc; Barthélemy, Dorothy (Frontiers in Neural Circuits, 2023)
Asymmetrical gait is a persistent deficit following neurological impairments, and one that is difficult to treat. Evidence suggests that sensory cues, such as asymmetrical somatosensory signals provided by a split-belt treadmill could reduce gait asymmetry. Modulating other sensory cues, such as vestibular afferents, also has the potential to address gait asymmetry. Notably, Galvanic vestibular stimulation (GVS), a non-invasive technique, can induce asymmetrical muscle responses in the lower limbs, but the extent of its effect on the gait pattern and gait symmetry are not known. Objective: Determine the influence of GVS on EMG pattern and cycle duration during walking in healthy young participants. Methods: Fifteen right-handed individuals participated in the study. Electromyography (EMG) recordings of bilateral soleus (SOL) and tibialis anterior (TA) were performed. First, to determine stimulation intensity, an accelerometer put on the vertex recorded the amplitude of the head tilts evoked by GVS (1-4.5 mA, 200ms) to establish a motor threshold (T). Second, while participants walked on a treadmill, GVS was applied at the onset of the stance phase during treadmill gait with an intensity of 1T and 1.5T with the cathode behind the right (Rcathode) or left ear (Lcathode). Vestibular responses were averaged (n=30 stimuli) and analyzed. The mean duration of the stimulated cycle, the following cycle and control cycle were measured. Results: GVS mainly induced long-latency responses in R SOL, RTA and LTA. Only short-latency responses were triggered in L SOL. Whereas responses in RSOL, LSOL and LTA were polarity-dependent, being facilitatory with Rcathode and inhibitory with Lcathode, response in RTA remained facilitatory regardless of the polarity. With Rcathode configuration, the stimulated cycle was prolonged compared to control cycle (p1T=0.03 and p1.5T= 0.03), due to prolonged LSOL and LTA EMG bursts (LSOL: p1T=0.008, p1.5T= 0.004, LTA: p1T= 0.035, p1.5T= 0.002). with Lcathode, GVS did not modify cycle duration. Conclusion: A brief, low-intensity GVS pulse delivered with a Rcathode configuration at the stance onset increases the duration of the stimulated gait cycle by prolonging EMG activity on the anodic side. A similar approach could be explored to influence gait symmetry in individuals with asymmetrical gait.